USM-TUT INTENSIFIES GLOBAL COLLABORATIONS WITH MoA SIGNING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 17 August 2016 Universiti Sains Malaysia (USM) and Toyohashi University of Technology (TUT) Japan intensified their global collaborations when both institutions signed a Memorandum of Agreement (MoA) to embark on a research project involving the mitigation of heavy metals, to detect and eliminate heavy metals in the environment using nanotechnology and nanomaterials.